A Novel Method for Blunting the Leading Edge of Waverider with Specified Curvature. (21st December 2020) - Fu, Xiang; Liu, Jun; Ding, Feng; Wang, Shengye; Dou, Tianheng
Abstract : An ideal waverider has an infinite sharp leading edge, which causes difficulty for manufacture and aerothermal protection. Therefore, the leading edge of the waverider must be blunted. For this purpose, a parametric method for blunting the leading edge of the waverider is proposed here, which can fulfill the goals of setting a leading-edge blunt radius, achieving geometric continuity, and realizing the parametric design. First is the blunting procedure of the proposed method incorporating the construction of two-dimensional blunt curves and the integration of these curves on a three-dimensional waverider configuration. Second, waveriders blunted with different geometric continuities are built with corresponding computing grids generated. Numerical methods are then introduced and validated by the benchmark cases. Finally, results from these blunted configurations are presented and compared in terms of their geometric and flow characteristics. It shows that the proposed method has a better performance in the head region of the waverider and is thereby more suitable for the practical design.